PENYELESAIAN SENGKETA DI LAUT NATUNA UTARA - Novianto, Rizal Dwi; Firmansyah, Dimas Agung; Pratama, Naufal Adi (Jurnal Hukum Bisnis Bonum Commune, 2020)
Indonesia is arguably one of the countries could be threatened by losses due to the action of China that illustrates or made nine points of new territory for the Natuna islands in the Riau Islands. Which of course with the threat of the Chinese state, will have a very significant effect on the Indonesian state. Can be seen in the gas-rich waters were impressed or seen to enter the territory of China's sovereignty. Judging from the legal aspect (juridical), the handling of the outer small islands currently requires an adequate, adequate set of laws in order to defend the territory and empower the conditions that occur. Reviewing various laws and regulations such as laws, government regulations, Presidential Decrees, and others relating to the handling or determination of boun-daries and borders of the State, including land areas and sea boundaries which when it becomes urgent or needed.Indonesia dapat dibilang salah satu Negara bisa saja terancam kerugian karena adanya aksi dari Cina yang menggambarkan atau membuat Sembilan titik wilayah-wilayah baru untuk kepulauan Natuna di Kepulauan Riau. Yang mana tentu dengan ancaman negara Cina tersebut, akan memberikan efekyang sangat berarti bagi negara Indonesia. Dapat dilihat dalam perairan kaya gas itu terkesan atau terlihat masuk wilayah kedaulatan China. Ditinjau dari aspek hukum (yuridis), penanganan dari pulau-pulau kecil terluar saat ini membutuhkan perangkat perundangundangan yang mencukupi, memadai dalam rangka mempertahankan wilayah dan memberdayakan keadaan yang terjadi. Peninjauan berbagai peraturan perundangundangan seperti Undang-undang, Peraturan pemerintah, Kepres, dan lain-lainnya yang berkaitan dengan penanganan atau penentuan batas dan perbatasan dari Negara baik mencakup wilayah darat maupun batas laut yang pada saat menjadi hal yang mendesak atau dibutuhkan.